Perspektif Global Penelitian untuk Pembangunan: Antisipasi Lingkungan Strategis dan Agenda R&D Pertanian - I Wayan Rusastra (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2012)
EnglishIn the globalization context the perspective contribution and redefinition of agricultural sector are changing. The multifunctional roles and inclusiveness of agriculture become stronger with their ultimate goals as a source of growth and employment, food security enhancement and poverty alleviation, as well as sustaining natural resources and agricultural development. Two fundamental global trends to take into account are inter-temporal strategic environment and anticipative agricultural R&D for development. Global strategic environment consists of biofuel development, climate change, sustainable agriculture, gender mainstreaming, and food-fuel-financial crises. On the other hand, the anticipative agricultural R&D global to get more attention is international trade transparency, technology role and food demand, incentive and investment reformation, structural transformation, and the harmonization of food security and food sovereignty development. Both aspects should be adapted and synergized in the thematic program planning and priority setting of agricultural research for development. The end target is the relevancy and effectiveness of agricultural research and achievement of agricultural development. IndonesianDalam perspektif global, telah terjadi pergeseran kontribusi dan redifinisi peran multifungsi sektor pertanian. Urgensi tentang multifungsi dan inklusifitas peran sektor pertanian semakin menguat, dengan sasaran sebagai sumber pertumbuhan dan kesempatan kerja, ketahanan pangan dan pengentasan kemiskinan, pelestarian sumberdaya dan keberlanjutan pembangunan pertanian. Dua perkembangan fundamental global yang perlu dipertimbangkan adalah dinamika lingkungan strategis dan R&D pertanian untuk pembangunan. Dinamika lingkungan strategis global mencakup pengembangan biofuel, perubahan iklim, pertanian berkelanjutan, pengarusutamaan gender, serta krisis energi, pangan, dan finansial global. Sementara itu antisipasi R&D pertanian global yang perlu dipertimbangkan adalah transparansi perdagangan, peran iptek dan kebutuhan pangan, reformasi insentif dan investasi, transformasi struktural, serta harmonisasi ketahanan pangan dan kedaulatan pangan. Kedua aspek tersebut perlu diadaptasikan dan disinergikan dalam perumusan program tematik dan penetapan skala prioritas R&D pertanian untuk pembangunan. Sasaran akhirnya adalah relevansi dan efektifitas R&D dan keberhasilan pembangunan pertanian nasional.